Effects of Complex System Topology on the Bak-Sneppen Evolution Model (Communications in Computational Physics, 2010)
In this paper, we investigate by numerical simulations the Bak-Sneppenmodel (BSM) for biological evolution on scale-free networks (SFNs) with various degreeexponents γ. We find that the punctuated equilibrium is rather robust with respectto the network topology. Furthermore, we analyze the evolution of the criticalaverage fitness ∗ and the exponent τ of 0 avalanche as a function of α (i.e., the degreeexponent γ). Our observations indicate the dependence of evolutionary dynamicsof BSM on the complex biosystem topology.